THE EFFECT OF COMBINED α1-ADRENERGIC BLOCKERS AND PDE-5 INHIBITORS THERAPY ON IPSS, IIEF-5, QMAX AND PVR PATIENTS BPH WITH LUTS AND ERECTILE DYSFUNCTION - Ridha, Muhammad; Hardjowijoto, Sunaryo; Renaldo, Johan (Indonesian Urological Association, 2017)
Purpose: Assess the efficacy of combined α1-adrenergic blocker (tamsulosin 0,4 mg) and PDE5 inhibitor (tadalafil 5 mg) therapy compared to tadalafil or tamsulosin alone in treating patient BPH with LUTS and ED. Material and methods: A randomised, double blind experimental study assessed 36 sexually active men with ED and LUTS suggestive of BPH. All patients were randomized to 3 groups: tamsulosin 0,4 mg (n=12), tadalafil 5mg (n=12), and combination of tamsulosin 0,4 mg and tadalafil 5 mg (n= 12), once daily for 6 weeks. Changed in IPSS scores and QoL index, IIEF-5 scores, Qmax, PVR and blood pressure were assessed and compared to baseline. Complication and serious adverse event were also monitored. Outcomes were assessed using ranked analysis of variance (ANOVA) and Kruskall-Wallis depends on data distribution and homogenity.Results: Tamsulosin 0,4 mg once daily for 6 weeks were significantly improved IPSS score and QoL index and Qmax from baseline. Tadalafil 5 mg once daily for 6 weeks were significantly improved IPSS score, QoL index and IIEF-5 index from baseline. Combined tamsulosin and tadalafil therapy were significantly improved IPSS score, QoL index, IIEF-5 index and Qmax from baseline. Significantly better improvement on IIEF-5 dan Qmax from baseline were observed on the combination of tamsulosin and tadalafil compared to monotherapy with tamsulosin or tadalafil after 6 weeks in patients BPH with LUTS and erectile dysfunction. There was no significant decreased in systolic and diastolic blood pressure from combined treatment compared to single treatment.Conclusions: Combined tamsulosin and tadalafil therapy was significantly better in improving IIEF aObjective: Assess the efficacy of combined α1-adrenergic blocker (tamsulosin 0.4 mg) and PDE5 inhibitor (tadalafil 5 mg) therapy compared to tadalafil or tamsulosin alone in treating patient Benign Prostate Hyperplasia (BPH) with lower urinary tract symptom (LUTS) and erectile dysfunction (ED). Material & methods: A randomised, double blind experimental study assessed 36 sexually active men with ED and LUTS suggestive of BPH. All patients were randomized to 3 groups: tamsulosin 0.4 mg (n=12), tadalafil 5mg (n=12), and combination of tamsulosin 0.4 mg and tadalafil 5 mg (n= 12), once daily for 6 weeks. Changed in IPSS scores and QoL index, IIEF-5 scores, Qmax, PVR and blood pressure were assessed and compared to baseline. Complication and serious adverse event were also monitored. Outcomes were assessed using ranked analysis of variance (ANOVA) and Kruskall-Wallis depends on data distribution and homogenity. Results: Tamsulosin 0.4 mg once daily for 6 weeks were significantly improved IPSS score, QoL index and Qmax from baseline. Tadalafil 5 mg once daily for 6 weeks were significantly improved IPSS score, QoL index and IIEF-5 index from baseline. Combined tamsulosin and tadalafil therapy were significantly improved IPSS score, QoL index, IIEF-5 index and Qmax from baseline. Significantly better improvement on IIEF-5 dan Qmax from baseline were observed on the combination of tamsulosin and tadalafil compared to monotherapy with tamsulosin or tadalafil after 6 weeks in patients BPH with LUTS and erectile dysfunction. There was no significant decreased in systolic and diastolic blood pressure from combined treatment compared to single treatment. Conclusion: Combined tamsulosin and tadalafil therapy was significantly better in improving IIEF and Qmax, but not significantly better in improving IPSS and PVR compared to monotherapy with tamsulosin or tadalafil alone. Combined therapy was well tolerated without serious adverse effect.nd Qmax, but not significantly better in improving IPSS and PVR compared to monotherapy with tamsulosin or tadalafil alone. Combined therapy was well tolerated without serious adverse effect.